Fashion Students' Perception of QR Code Innovation in Argenta Nala Fashion Design - Aini, Intan nur; Rachmawati, Rina (Universitas Negeri Semarang, 2026)
The development of digital technology encourages the birth of new innovations in the field of fashion design, one of which is through the use of Quick Response (QR) Code as an information medium and visual elements. This innovation not only serves as a means of accessing information, but also has the potential to enrich user experience, and innovative value in fashion products. This study aims to analyze the perception of Fashion Designers students towards the innovation of implementing QR Code in Argenta Nala fashion design, by reviewing the aspects of ease of use, readability, completeness of information, user experience, and clarity of appearance. The study uses a quantitative approach with a percentage descriptive method. Data was collected through the distribution of a closed questionnaire based on the Likert scale to Fashion Designers students who had taken the Tailoring course as research respondents by calculating the percentage of data to find out the respondents' perception tendencies. The results of the study show that the application of QR Code in Argenta Nala fashion design received positive perceptions from students, with a good to very good rating category on all indicators assessed with an average percentage of 92%. QR Codes are considered easy to use, easy to scan, able to present clear information, and provide an experience to users without overriding fashion aesthetics. This study concludes that QR Code has great potential to be developed into an effective information and product recognition medium in the development of technology-based designs that are functional and user experience-oriented, especially in the context of Fashion Design.